Evaluation of p53 codon 72 polymorphism in adenocarcinomas of the colon and rectum in La Plata, Argentina - Perez, Luis Orlando (2006)
Aim: To evaluate the potential association between p53 codon 72 polymorphism and sporadic colorectal adenocarcinoma development, and human papillomavirus (HPV) infection. Methods: One-hundred and nine controls and 53 patients with colon cancer from the city of La Plata, Argentina were analyzed. p53 codon 72 genotypes and HPV infection were identified using allele-specific polymerase chain reaction and nested polymerase chain reaction, respectively. Results: The differences in the distribution of p53 codon 72 polymorphism between the cases and controls were statistically significant. The arginine allele had a prevalence of 0.65 in controls and 0.77 in cases. The corresponding odds ratio for the homozygous arginine genotype was 2.08 (95% CI, 1.06-4.05; P<0.05). Lack of association was found between p53 polymorphism and HPV infection in the set of adenocarcinomas. Conclusion: The findings of the present study indicate that p53 codon 72 arginine homozygous genotype may represent a genetic predisposing factor for colon cancer development. However, further studies are needed in order to elucidate the role of p53 codon 72 polymorphism in colorectal cancer.